Impact of reirradiation, chemotherapy, and immunotherapy on survival of patients with recurrent lung cancer: A single‐center retrospective analysis. Issue 8 (14th February 2021) - Grambozov, Brane; Wass, Romana; Stana, Markus; Gerum, Sabine; Karner, Josef; Fastner, Gerd; Studnicka, Michael; Sedlmayer, Felix; Zehentmayr, Franz
Abstract: Background: Given the limited curative treatment options for recurrent lung cancer patients, the aim of our retrospective study was to investigate whether these patients would benefit in terms of overall survival (OS) by adding immunotherapy to high‐dose reirradiation. Materials and methods: Between 2013 and 2019, 47 consecutive patients with in‐field tumor recurrence underwent high‐dose thoracic reirradiation at our institute. Twenty patients (43%) received high‐dose reirradiation only, while 27/47 (57%) additionally had systemic therapy (immunotherapy and/or chemotherapy). With the exception of one patent, the interval between first and second radiation was at least 9 months. All patients had an Eastern cooperative oncology group ≤2. The diagnostic work‐up included a mandatory fluorodeoxyglucose‐positron emission tomography‐computed tomography scan and histological verification. The primary endpoint was OS after completion of the second course of irradiation. Results: In the whole cohort of 47 patients, the median overall survival (mOS) after reirradiation was 18.9 months (95% confidence interval [CI] 16.5–21.3 months), while in the subgroup of 27 patients who received additional systemic treatment after reirradiation, mOS amounted to 21.8 months (95% CI 17.8–25.8 months). Within this group the comparison between reirradiation combined with either immunotherapy ( n = 21) or chemotherapy ( n = 6) revealed a difference in OS, which was in favor of the first (log‐rank p value = 0.063). Three patients (11%) experienced acute side effects and one (4%) showed a late hemorrhage grade 3. Conclusion: Patients who received immunotherapy and reirradiation lived longer than those who did not receive immunotherapy. Abstract : The aim of our retrospective study was to investigate whether reccurrent lung patients would benefit in terms of overall survival by adding immunotherapy to high‐dose reirradiation. Between 2013 and 2019, 47 consecutive patients with in‐field tumor recurrence underwent high‐dose thoracic reirradiation at our institute. Twenty patients (43%) received high dose reirradiation only, while 27/47 (57%) additionally had systemic therapy (immunotherapy and/or chemotherapy). Patients who received immunotherapy and reirradiation lived longer than those who did not receive immunotherapy.